Prehabilitation in the era of minimally invasive thoracic surgery: a narrative review of evidence, implementation, and future directions - Guart, Jiddu; Assaad, Jonathan; Shafique, Samih; Palleiko, Benjamin A.; Kim, Hee-Jung Janice; Uy, Karl; Maxfield, Mark W. (Video-Assisted Thoracic Surgery, 2026)
Prehabilitation aims to enhance a patient’s physiological reserve before surgery to improve postoperative outcomes. Increasingly, prehabilitation complements enhanced recovery after surgery (ERAS) pathways in thoracic surgery by addressing multiple domains of preoperative fitness, including aerobic and resistance exercises, respiratory conditioning, nutritional optimization, psychological support, risk factor modification, and patient education. This narrative review synthesizes current evidence on prehabilitation for patients undergoing various surgical procedures, and possible implementation strategies and future directions in thoracic surgery with an emphasis on minimally invasive surgical approaches.